SOME TENTATIVE PROPOSITIONS UNDERLYING CONSOLIDATED REPORTS. - Kohler, E. L. (The Accounting Review, 1938)
Abstract The article presents some tentative propositions underlying consolidated reports. Consolidated financial statements, like other human institutions, have enjoyed varying degrees of popularity. From obscure beginnings they rose to a position of eminence in the financial world and were quite generally regarded as the only acceptable means by which the financial data of related business organizations could be presented to creditors, stockholders, income-tax authorities, and the public. Both the strength and the weakness of a consolidated statement lie in its ability to disclose summary information about a number of related enterprises, with a fine disregard for legal entities. Separate financial statements of individual subsidiaries must be submitted to outside stockholders if they are to be given any idea of the significance of their equities, consolidated statements mean nothing to them except insofar as a controlled profit lies in assets not yet disposed of to the public. Conditions may make one or more types of combined financial statements desirable in the published report of a controlling company. These are the overall consolidated statements, group statements of all the subsidiaries or of natural divisions of subsidiaries, and consolidating or grouping statements.